Motherhood and gender wage differentials within a Chinese firm - Chen, Yi Zhang, Hong and Zhou, Li-An (Economic Development and Cultural Change)
The within-firm gender wage gap is an important part of the overall gender gap in the labor market. This paper describes how parenthood is associated with the within-firm gender gap using a personnel data set from a large Chinese company. The wage gap is small in the early stages of careers and becomes increasingly evident when female employees get married and have children. Whereas the short-term peak around childbirth can be explained by women$1 (Breduced working hours, the long-term trend is caused by women$1 (Bs concentration in lower-level jobs. Our study highlights the importance of internal gender segregation in understanding gender differentials.- Reproduced s